2001
DOI: 10.1097/00001610-200105000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Does a Physically Active Lifestyle Improve Symptoms in Women With Irritable Bowel Syndrome?

Abstract: The ethics of dealing with the provision of nutritional therapies has been complicated by technological advances that have affected all of medical science. As a result, nurses are increasingly confronted with decisions regarding the provision of invasive treatments. Indeed, enormous faith is invested in the ability and wisdom of healthcare professionals to alleviate suffering and accomplish cure through the application of invasive therapeutic interventions such as percutaneous endoscopic gastrostomy (PEG) plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…Lustyk et al [24] reported that the IBS group had less exercise than the non-IBS group in the general population in America (p = 0.05). Kim and Ban [25] also reported that the IBS group tended to have less exercise time a week than the non-IBS group in Korean college students.…”
Section: Discussionmentioning
confidence: 99%
“…Lustyk et al [24] reported that the IBS group had less exercise than the non-IBS group in the general population in America (p = 0.05). Kim and Ban [25] also reported that the IBS group tended to have less exercise time a week than the non-IBS group in Korean college students.…”
Section: Discussionmentioning
confidence: 99%
“…Daily exercise can maintain a good bowel function and help to prevent constipation (7). Lustyk et al reported that physically active women were less likely to report a feeling of incomplete evacuation following a bowel movement than inactive women (25). Okami et al reported that an IBS group exercised less than a non-IBS group among Japanese nursing and medical school students (11).…”
Section: Discussionmentioning
confidence: 99%
“…16 groups of investigators [5,6,11,16,27,36,42,43,50,53,59,60,67,70,72,74] have evaluated habitual physical activity in patients from various age groups and with variously defined CIBD, using subjective and objective measures of physical activity that have included occupational categorization, completion of interviews or questionnaires, accelerometry and use of other objective sensors ( • ▶ Table 1). 12 of the 16 studies found levels of physical activity that were significantly lower in patients with CIBD than in controls, the difference generally being more marked for those classed as CD than for those with UC ( [27,43,53] but not [16]).…”
Section: Current Levels Of Habitual Physical Activity In Ibdmentioning
confidence: 99%